PENGEMBANGAN MODEL KOMUNIKASI PERSUASIF PEMUDADESA ADAT CIPTAGELAR DALAM KEGIATAN AGROFORESTRI BERBASIS KASEPUHAN - Fajrini, Nurkhalila; Mujtahid, Iqbal Miftakhul (Universitas Muhammadiyah Jakarta, 2024)
Forest sustainability will be if the ecological and economic functions of the forest can take place appropriately. The sustainability of the two purposes of the forest requires community participation through persuasive communication. Kasepuhan Ciptagelar presented that community participation in environmental activities, especially agroforestry, is also represented by young people. Therefore, this research aims to identify Persuasive Communication of Ciptagelar Traditional Village Youth in Agroforestry Activities in Kasepuhan Ciptagelar, Sirnaresmi, Sukabumi Regency, West Java Province. This research used a constructivist paradigm and a qualitative descriptive approach. The study highlights every form of persuasive communication in agroforestry activities by Ciptagelar Indigenous youth. The results showed that the persuasive communication carried out by the Ciptagelar Indigenous Youth used a behavioral intention approach. All forms of persuasive communication actions in Kasepuhan-based Agroforestry activities. Uniquely, the youths are very obedient to customary rules, but also use the latest communication media in persuasive communication. Persuasive communication that is carried out only aims at cognitive aspects for external parties in the Village. The concept of kasepuhan which is carried out in every form of persuasive communication by Ciptagelar Traditional Village Youth to external village audiences carries the principles of trust and volunteerism.